2017
DOI: 10.1038/srep46160
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of archaea at fine spatial scales in Shark Bay mat microbiomes

Abstract: The role of archaea in microbial mats is poorly understood. Delineating the spatial distribution of archaea with mat depth will enable resolution of putative niches in these systems. In the present study, high throughput amplicon sequencing was undertaken in conjunction with analysis of key biogeochemical properties of two mats (smooth and pustular) from Shark Bay, Australia. One-way analysis of similarity tests indicated the archaeal community structures of smooth and pustular mats were significantly differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 86 publications
9
67
0
Order By: Relevance
“…Furthermore, Shark Bay microbial mats are subject to hypersalinity of more than 60 PSU [3,5], desiccation stress, and high UV radiation [18,19]. Daily tidal cycles also cause fluctuations in salinity and temperature at a local scale in the mat microenvironment [20,21], adding another dimension to the extreme conditions present. The Shark Bay microbial mat systems are thus considered as an ecological model for understanding stress response and resilience in microbial ecosystems, as well as a window to the past.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Shark Bay microbial mats are subject to hypersalinity of more than 60 PSU [3,5], desiccation stress, and high UV radiation [18,19]. Daily tidal cycles also cause fluctuations in salinity and temperature at a local scale in the mat microenvironment [20,21], adding another dimension to the extreme conditions present. The Shark Bay microbial mat systems are thus considered as an ecological model for understanding stress response and resilience in microbial ecosystems, as well as a window to the past.…”
Section: Introductionmentioning
confidence: 99%
“…Early work in Shark Bay has focused primarily on understanding microbial diversity using targeted culturing and cloning/sequencing of 16S rDNA PCR products [2,4]. These studies proposed the Shark Bay systems were dominated by Proteobacteria, Bacteroidetes, Cyanobacteria, and Haloarchaea [2,4], and, more recently, deep iTag amplicon sequencing has revealed another dominant clade -Chloroflexi-as well as novel members, including OP8, GN04, and Parvarchaeota [3,21,22]. These latter studies were coupled with microelectrode measurements in Shark Bay and indicated a steep biogeochemical gradient with vertical depth in the microbial mats (O 2 , H 2 S, CH 4 ) [3,21,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern microbialites have been extensively studied using lipid biomarker analysis, gene sequencing, isotopic analysis, growth experiments, and microelectrode measurements from a wide range of sites, including Shark Bay in Western Australia (Allen, Neilan, Burns, Jahnke, & Summons, 2010;Goh et al, 2009;Grice et al, 2014;Ruvindy, White, Neilan, & Burns, 2015;Wong, Smith, Visscher, & Burns, 2015;Wong et al, 2017), the Bahamas (Andres & Pamela Reid, 2006;Baumgartner et al, 2006;Dupraz, Fowler, Tobias, & Visscher, 2013;Mobberley et al, 2015;Paerl, Steppe, & Reid, 2001;Reid et al, 2000;Visscher et al, 1998), Yellowstone National Park USA (Jahnke et al, 2004;Osburn, Sessions, Pepe-Ranney, & Spear, 2011;Pepe-Ranney et al, 2012), Pavilion Lake in British Columbia Canada (Brady, Laval, Lim, & Slater, 2014;Russell et al, 2014;White et al, 2016), the Antarctic McMurdo Ice Shelf (Jungblut, Allen, Burns, & Neilan, 2009), and Alchichica, Mexico (Breitbart et al, 2009;Couradeau et al, 2011). The study of modern microbialites enhances our understanding of ancient analogs by connecting explicit biosignatures such as DNA and RNA sequences and aqueous geochemistry to those that are preserved over geologic time such as carbonate morphology and lipid biomarkers.…”
mentioning
confidence: 99%
“…Despite their strikingly different morphologies, these mats share many bacterial, archaeal and eukaryotic phyla (Allen et al, 2009). Recent community sequencing analyses have characterized in particular the bacterial and archaeal functional diversity of Hamelin Pool microbial mats (Wong et al, 2015;Wong et al, 2017;Wong et al, 2018), with a range of different phototrophs present. The smooth mats feature a smooth, light brown surface while pustular mats are characterized by a dark pigmented and pustular surface layer.…”
Section: Introductionmentioning
confidence: 99%